Analisis Modus Operandi Kejahatan Perjudian Online - Elpin Sulingo; Dian Ekawaty ismail; Vifi Swarianata (Universitas Sains dan Teknologi Komputer, 2023)
The background of this research is the modus operandi of online gambling crimes. The problem is the rise of online gambling among the public. Gambling via the internet (internet gambling) usually occurs because of placing bets on sports activities or casinos via the internet. The perpetrators of online gambling can be punished under Article 27 paragraph (2) jo. Article 45 paragraph (2) of Law Number 19 of 2016 concerning Information and Electronic Transactions. Online games are actually the whole process, be it betting, playing or collecting money via the internet. The practice of online gambling is carried out by carrying out transactions in the form of selling chips which are then offered and purchased by other people or certain agents to be sold/transferred to other interested poker accounts. These pins and chips will be sold at a certain price in cash (cash) in the form of money (rupiah). The regulation of online soccer gambling crimes in Indonesia is regulated in Law Number 19 of 2016 concerning Information and Electronic Transactions to be precise in Article 27 paragraph (2) and for the regulation of criminal acts it is regulated in Article 45 of the Information Law and electronic transactions. the application of criminal sanctions to the perpetrators of gambling crimes. The purpose of this study is to determine the modus operandi analysis of online gambling crimes. This research uses the Empirical Legal Research method. The results of the study concluded that (1) Analysis of the modus operandi of online gambling crimes. (2) Obstacles in handling the modus operandi of online gambling crimes.